Hybrid Protein between Ribosomal Protein S16 and RimM of Escherichia coli Retains the Ribosome Maturation Function of Both Proteins - Lövgren, J. Mattias (American Society for Microbiology, 2001)
The RimM protein in Escherichia coli is associated with free 30S ribosomal subunits but not with 70S ribosomes and is important for efficient maturation of the 30S subunits. A mutant lacking RimM shows a sevenfold-reduced growth rate and a reduced translational efficiency. Here we show that a double alanine-for-tyrosine substitution in RimM prevents it from associating with the 30S subunits and reduces the growth rate of E. coli approximately threefold. Several faster-growing derivatives of the rimM amino acid substitution mutant were found that contain suppressor mutations which increased the amount of the RimM protein by two different mechanisms. Most of the suppressor mutations destabilized a secondary structure in the rimM mRNA, which previously was shown to decrease the synthesis of RimM by preventing the access of the ribosomes to the translation initiation region on the rimM mRNA. Three other independently isolated suppressor mutations created a fusion between rpsP, encoding the ribosomal protein S16, and rimM on the chromosome as a result of mutations in the rpsP stop codon preceding rimM. A severalfold-higher amount of the produced hybrid S16-RimM protein in the suppressor strains than of the native-sized RimM in the original substitution mutant seems to explain the suppression. The S16-RimM protein but not any native-size ribosomal protein S16 was found both in free 30S ribosomal subunits and in translationally active 70S ribosomes of the suppressor strains. This suggests that the hybrid protein can substitute for S16, which is an essential protein probably because of its role in ribosome assembly. Thus, the S16-RimM hybrid protein seems capable of carrying out the important functions that native S16 and RimM have in ribosome biogenesis.